He loves me, he loves me not - Mayhall, Robin; Cella, Kristen (Minneapolis Graphic Universe, 2013)
Upon moving to small-town Texas part-way into her junior year of high school, Serena sees parallels between the novel her class is studying, Dr. Jekyll and Mr. Hyde, and the two men in her life: boyfriend Lance, the quarterback, and outsider Cam
Marsa
5 18 21 22
Keywords: Family life -- Texas -- Fiction; Horror stories; Moving, Household -- Fiction